Sociolinguistic Study of Arabic Language Use in the Markaz Arabiyah Islamic Boarding School Environment: Indonesia - Nida, Nida Husna Fahimah; Nurfitri, Hanifah; Tatang (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the use of language in the Markaz Arabiyah Islamic boarding school, located in Pare, East Java. In this context, the phenomenon of the use of Arabic and Indonesian in the daily interactions of students is the main focus. This research method uses a qualitative approach with a case study in the Markaz Arabiyah Islamic boarding school, combining direct observation and surveys to obtain in-depth data on the use of Arabic and Indonesian in the daily interactions of students. The results of the study indicate that in the Markaz Arabiyah Islamic boarding school there is a pattern of bilingualism, where Arabic is used in formal contexts, while Indonesian dominates informal communication. This pattern supports Arabic language learning, strengthens religious values, and maintains the national identity and social ties of students. As many as 65% of students stated that they were interested in using Arabic in their daily lives. They believe that this language can deepen their understanding and increase their religiosity. The students believe that by interacting more often using Arabic, they can more easily absorb religious values ​​and improve their spiritual quality. This study is expected to contribute to the understanding of language use in the context of religious education.